Improvement Achieved By the World Bank Financed Project for Chemical Engineering Education in Indonesia - Sanggono Adisasmito (International Mineral Processing Congress, 2003)
"The quality of the higher education in Indonesia is being improved by implementing a program financed by the World Bank under a project named QUE (Quality for Undergraduate Education). The investments are provided to selected study programs through a competitive selection process. The grant finances staff development, the purchase of equipments, textbooks, consumables, technical assistance, and incentives for outstanding faculties such as teaching grants, project grants, lecture note awards, and educational policy studies. These additional investments are provided to produce chemical engineering graduates that will compete beyond the national market.Chemical Engineering Department of Institut Teknologi Bandung in Indonesia has been selected to receive the QUE grant beginning the year 2000 and ending the year 2004. The department is actively involved in the mineral processing issues, particularly in the aspects of energy supply and the environmental protection. The activities are distributed in different laboratories and areas of expertise, such as: thermodynamics and utility systems, process equipment, chemical reaction and catalysis, microbiology and bioprocess engineering, process control, ceramics, as well as polymer and membrane technology. The main objectives of the QUE project are to improve the undergraduate program in the following aspects: Relevance, Academic atmosphere, Institutional management and commitment, Sustainability, as well as Efficiency and productivity, or abbreviated as RAISE. At the end of every fiscal year, the progress of the program is evaluated to measure the effectiveness of the project.The achievement of the QUE project objectives were assessed using performance indicators developed during the program design. There are six indicators to measure the performance of the individual program of study, such as: (1) Admission Test score, (2) average students' Grade Point Average (GPA), (3) average graduates' length of study, (4) graduates' waiting time before getting first job, (5) Test of English as Foreign Language (TOEFL) score, (6) Graduate Record Examination (GRE) score. Essentially, the RAISE evaluation criteria will be used to perform three main functions, such as (1) to measure the achievement through the six quantitative performance indicators, (2) to support the progress of evaluation and reporting throughout the implementation of the program, (3) to provide a universal framework for qualitative evaluation."